Between Compliance and Accountability: Exploring the Supply–Demand Gap in Sustainability Reporting of Jayapura City Government - Klara Wonar; Agustinus Salle; Putri Ratnasari; Betrix S.F. Mami (Green Publisher Indonesia, 2025)
This paper investigates sustainability reporting (SR) practices in Jayapura City Government, Papua, by examining the gap between the supply side (civil servants) and the demand side (citizens). It aims to assess whether current reporting practices align with international standards, such as the Global Reporting Initiative (GRI), and whether they meet stakeholder expectations. A mixed-methods design was adopted. Primary data were collected from surveys of 45 government officials and 45 citizens, while secondary data came from budget documents, performance reports, and relevant regulations. Quantitative data were analyzed descriptively, and qualitative data were explored through thematic and content analysis. The analysis was guided by legitimacy, stakeholder, institutional, and signaling theories. The study reveals a significant supply–demand gap. Civil servants perceive existing reports as sufficient from a compliance perspective, whereas citizens demand broader disclosures on social, governance, and especially environmental issues. The absence of a formal GRI-based SR indicates that reporting remains administrative rather than strategic. Citizens in particular view the use of Special Autonomy Funds as non-transparent, further eroding trust in government reporting. This paper contributes to public sector SR literature by introducing the underexplored context of Papua, Indonesia. It demonstrates how multiple theoretical frameworks explain the supply– demand gap in a developing country setting and highlights the socio-political and institutional barriers to SR adoption. The findings also offer practical insights for policymakers by recommending capacity building for civil servants and integrating GRI-based indicators into existing local government reporting frameworks.